Eksplorasi Ketersediaan Teknologi dan Sistem Informasi Sebagai Penunjang Mutu Layanan Perpustakaan IAIN Curup - Permanasari, Revi; Elizah, Tenti; Warlizasusi, Jumira; Sahib, Abdul (Indonesian Journal of Islamic Educational Management, 2024)
Libraries play a crucial role in education and research in higher education institutions. In the digital era, technology and information systems have become essential to strengthen the role of libraries as efficient and effective information centers. However, studies on the application of technology and information systems in the context of libraries in Islamic higher education environments are still limited. This research aims to explore the availability and application of technology and information systems in library services at the Curup State Islamic Institute (IAIN). The focus is to analyze the profile of available technology and information systems and the extent to which they are utilized in improving the quality of library services. This research uses a qualitative approach with data collection techniques in the form of direct observation, in-depth interviews, field recording, visual documentation and document analysis. Research subjects were selected using Random Sampling techniques, involving library users as informants. Data were analyzed descriptively-narratively to provide an in-depth picture of the condition of technology and information systems and their influence on the quality of library services. The research results show that the IAIN Curup Library UPT has adequate technological facilities and information systems, such as computers, internet networks, attendance information systems, and the Online Public Access Catalog (OPAC). Users feel the effectiveness and efficiency of library services, although there are still needs for improvement, such as digitizing collections and optimizing the library management system. Technology integration has had a positive impact on library management efficiency and user experience at IAIN Curup